Evaluation, characterisation and modelling of Aspergillus flavus in aflatoxin production in peanuts along the supply chain - Mahror, Norlia (2019)
Aflatoxin contamination is a major food safety issue in raw peanuts and peanut-based products worldwide. Thus, an extensive study on aflatoxins and Aspergillus spp. in peanuts along the supply chain in Malaysia is needed in order to protect the consumers against the harmful effects of aflatoxins. Generally, this study was aimed to evaluate the aflatoxin contamination, identify, characterise and model the growth of aflatoxigenic A. flavus isolated from peanuts collected from the importers, manufacturers, and retailers. In the present study, aflatoxins were found to be significantly higher (p < 0.05) in raw peanuts and peanut-based products from the retailers (< LOD – 1021.4 μg/kg) followed by the manufacturers (< LOD – 181.9 μg/kg) while samples from the importers were free from aflatoxins. Total fungal count was relatively higher in raw peanuts (log 0.3 – 3.6 CFU/g) as compared to peanutbased products (log 0.6 – 2.3 CFU/g) in which samples from the importers recorded the highest contamination level for aflatoxigenic Aspergillus spp. (log 2.2 ± 1.1 CFU/g). On the basis of morphological, chemical, and molecular identification, all isolates were identified as Aspergillus section Flavi. Specifically, 127 isolates were confirmed as A. flavus, and one isolate as A. tamarii. Six chemotype profiles were proposed indicating the diversity of toxigenic potential. About 58.6%, 68.5%, and 100% of the isolates were positive for aflatoxin, cyclopiazonic acid and aspergillic acid production, respectively. The maximum likelihood (ML) phylogenetic tree using ITS and β-tubulin gene resolved the species into two different clades in which all A. flavus (both aflatoxigenic and non-aflatoxigenic) were grouped in the same clade and A. tamarii in a different clade. Aflatoxin biosynthesis genes namely aflR, aflP (omtA), aflD (nor-1), aflM (ver-1), and aflC (pksA) were detected in all aflatoxigenic A. flavus while the non-aflatoxigenic A. flavus failed to amplify at least one of the genes that was tested. The analysis of variance showed a significant effect of strain, temperature and water activity (aw) on the fungal growth and aflatoxin production (p < 0.05). The maximum growth rate, μmax (mm/day) of two aflatoxigenic A. flavus, (A8R and A82R) on PMEA was estimated by using the primary model of Baranyi and the μmax was then fitted to the secondary model; second order polynomial and linear Arrhenius-Davey to describe the growth rate as a function of temperature and aw. In general, the growth rate of A. flavus increased with increasing temperature and aw until reaching the optimum temperature and further increase in aw beyond this point resulted in decrease growth rate. The growth of A. flavus was observed at the minimum aw of 0.85 under the optimum temperature (32 – 33°C) and the minimum temperature of 20°C with 0.94 aw. A similar pattern was observed in aflatoxin production but in a narrower range of temperature (25 – 35°C) and aw (0.92 – 0.98 aw). In conclusion, A. flavus was the predominant species that contaminate peanuts and subsequently produce aflatoxins during the storage period. Therefore, proper storage structures and conditions for peanuts during storage are very important in order to control the growth of aflatoxigenic A. flavus and aflatoxin contamination.